Combinatorial analysis of population dynamics, metabolite levels and malolactic fermentation in Saccharomyces cerevisiae/ Lachancea thermotolerans mixed fermentations. (June 2021) - Fairbairn, S.; Engelbrecht, L.; Setati, M.E.; du Toit, M.; Bauer, F.F.; Divol, B.; Rossouw, D.
Abstract: The outcome of co- or sequential inoculation of Lachancea thermotolerans in winemaking remains unpredictable due to a lack of integrated data regarding the impact of grape juice composition on L. thermotolerans fermentation behaviour. Here, we investigate the impact of nitrogen composition on fermentation characteristics and aroma compound production in grape juice sequentially inoculated with commercial L. thermotolerans and S. cerevisiae strains. Subsequently, all treatments were subjected to malolactic fermentation (MLF) using two commercial strains of Oenococcus oeni . Addition of amino acids led to faster growth for S. cerevisiae fermentations, compared to the nitrogen-equivalent addition of diammonium phosphate (DAP). L. thermotolerans persistence in the mixed fermentations was significantly higher following DAP addition, with higher glycerol and lactic acid production. Interestingly, the lower total Nitrogen content in DAP-treated musts compared to other treatments did not alter the subsequent growth of S. cerevisiae . MLF was more similar between musts fermented with L. thermotolerans, regardless of nutrient regime, whereas significant differences in MLF completion times were observed for different nitrogen treatments in S. cerevisiae fermentations. Collectively, the data present an integrated view of the impact of nitrogen treatment on multispecies co-inoculation (growth kinetics and aromatic outcomes) and the downstream impact on MLF. Highlights: Integrated analysis of the co-inoculation of two yeast species and of nitrogen sources on fermentation and wine composition. L. thermotolerans reduces total nitrogen levels without affecting growth of sequentially inoculated S. cerevisiae . Volatile aroma production in response to addition of branched chain amino acids is similar in both yeast species. Amino acids that are preferred nitrogen sources lead to significantly higher acetic acid production in both yeast species . L. thermotolerans fermentations resulted in reduced overall medium chain fatty acids and ethyl esters.